Pengaruh Kemiskinan dan Kesempatan Kerja Terhadap Indeks Pembangunan Manusia di Provinsi Sulawesi Tenggara - M., Mutmainnah; Harafah, La Ode Muh.; Saranani, Fajar (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to analyze the effect of poverty and employment opportunities on the human development index (HDI) in Southeast Sulawesi Province. This study uses a quantitative approach with an explanatory research method. The data used in this study are poverty data (X1) and employment opportunities (X2) and the human development index (Y) in 17 regencies/cities in Southeast Sulawesi Province with an observation period of 5 years (2019-2023). The data analysis technique in this study is Panel Data Regression Analysis using Eviews 12. The results of the study show that poverty has a negative and insignificant effect on the Human Development Index (HDI) in Southeast Sulawesi Province. This shows that if poverty increases, the Human Development Index will decrease and employment opportunities have a positive and significant effect on the Human Development Index (HDI) variable in Southeast Sulawesi Province. This shows that if employment opportunities increase, the Human Development Index will also increase.